SYNTHESIZE AND CITOTOXICITY TEST OF SEVERAL COMPOUNDS OF MONO PARA-HIDROXY CHALCON - Indyah Sulistyo Arty (Indonesian Journal of Chemistry, 2010)
Five compounds of mono para-hidroxy chalcon were synthesized (TC1, TC2, TC3, TC4, and TC5) and tested their cytotoxicity against HeLa cell and Raji cell. The difference in substituent of TC1 (R4 =H), TC2 (R4 = OCH3), and TC3 (R4 = F), showed the difference of their citotoxicity against HeLa cell. The citotoxicity of TC1 (LC50 = 16.08 µg/mL) ≈ TC3 (LC50 = 13.37 µg/mL), but the substituent difference of TC2 (LC50 = 147.43 µg/mL), decreasing it citotoxicity 10 times. Like wise their citotoxicity against Raji cell of TC1 (LC50 = 36.44 µg/mL) ≈ TC3 (LC50 = 30.46 µg/mL), but the substituent difference of TC2 (LC50 = 468.94 µg/mL), decreasing it citotoxicity activity 15 times. Nevertheless the strength of citotoxicity TC4 (LC50 = 98.74 µg/mL) and TC5 (LC50 = 110.97 µg/mL) against Raji cell are stronger than the citotoxicity of two of them against HeLa cell (LC50 of TC4 = none, LC50 of TC5 = 576.53 µg/mL).